State as an Heir: Balancing Public and Private Interests in Georgia and Europe. Part I: Comparative Overview - Irakli Leonidze (Review of European and Comparative Law)
The Civil Code of Georgia establishes the state’s right to inherit heirless estates. According to the Georgian law, the state is referred to as the legal successor. Should we always consider the state as the legitimate successor, or is this only a necessity to maintain public order? Does the state have a legitimate public interest of heirless estate and how can this be balanced against the private interests? The following subjects will be discussed in this article from the perspectives of Georgia and European countries. The question of whether the state should assume ownership of the private property in the absence of heirs is a subject that has given rise to significant discourse on topics of justice, property rights, and the role of the state in private affairs. Numerous scholars have presented a range of arguments both in favour of and in opposition to the notion of the state becoming the recipient of property that lacks heirs. Given the legal nature of the problems, it is necessary to explicitly define the state’s status as a special legal heir in Article 1343 of the Civil Code of Georgia to prevent the confusion of rights and duties from leading to excessive state intervention in inheritance matters. European countries’ experience is very important for creating a new legal status of the state. Because of the problem of transferring an estate when there is no heir, balancing public and private interests is a most popular issue. The purpose of this paper is to examine the rights and obligations of the state as a legal heir under the different regulations and how these principles affect inheritance relations in socio-legal perspectives. It compares how this issue is addressed in other European countries’ legal systems and draws conclusions about the dual role of the state based on the different practice. This article aims to explore the theoretical possibilities about the state’s right on the heirless estate, offering valuable recommentations for the Constitutional Court of Georgia in justifying and making decisions on this issue.